Is there any influence of biodynamic preparation 501 on the physiological activity of grape leaves cv. Cesanese d’Affile? - Stefano Pettinelli; Laura Buzzi; Brunella Ceccantoni; Rosario Muleo; Alessandro Bianchi; Elena Brunori; Fabio Mencarelli (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background Biodynamic agriculture is a management approach that aims to reduce the reliance on agrochemicals for production by emphasizing the use of specific natural preparations. A 2-year field trial spanning 2019–2020 was conducted in an established vineyard (Vitis vinifera L., cv. Cesanese d’Affile) to elucidate the impact of the cow horn silica biodynamic preparation (BD-501) on leaf vine physiology, potential resistance via chitinase activity, and analysis of secondary metabolites. The vineyard under biodynamic management was divided into two plots: one treated with BD-501 (BD-501) and the other untreated (BD). Throughout the vine growth season, measurements of carotenoid and chlorophyll levels, polyphenols, and chitinase activity were taken around key phenological phases (BBCH scale). During the ripening phase, a fluorometer was employed to assess chlorophyll fluorescence in the leaves. Results Leaves treated with BD-501 exhibited elevated concentrations of polyphenols and increased chitinase activity during the later phenological phases. In contrast, the untreated BD samples demonstrated high values primarily in the central phase of the observation period but not consistently throughout. At the time of harvest, chlorophyll concentration and quantum yield exhibited no statistically significant differences. BD-501 triggered a distinct response in terms of potential defense mechanisms (elevated polyphenols and chitinase activity) during the veraison phase. However, conversely, lower levels of chlorophylls and carotenoids were observed. Conclusions Nevertheless, a further round of experimental work is required to thoroughly comprehend the regulatory mechanisms behind this adaptive response and to ascertain the efficacy of BD-501. Graphical Abstract